Technology Usage and Learning Outcomes of Students in the New Normal: Basis of Learning Continuity Plan - Maquipoten, Marelen; Perez, Rexomar (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
Technology in education plays a vital role, especially during the COVID-19 pandemic. Teachers can harness online learning as a powerful educational tool by integrating technology into existing curricula. Thus, this study determined the extent of technology usage and learning outcomes of the students in the different subjects in terms of the most essential learning competencies (MELCs). Moreover, significant differences and relationships were explored for further analysis. The results revealed that most of the students used technology to search and study their lessons, watched DEPED TV episodes to learn, participated in online courses, and answered modules. Additionally, usually installed apps on their phones, but they were unlikely to listen to the radio. As such, the student’s learning outcomes are significantly high across subject areas despite of difficulties experienced. Relatively, highly significant differences and relationships were seen in some areas in terms of variables for both usage and learning outcomes. Therefore, technology is a factor in education. It is then recommended to utilize the continuity plan for improvement.